A case report of severe pirimiphos-methyl intoxication: Clinical findings and cholinesterase status - Zellner, Tobias; Rabe, Christian; Wellen-Pawlowski, Jens von der; Hansen, Dagmar; John, Harald; Worek, Franz; Eyer, Florian (Frontiers in Pharmacology, 2022)
63-year-old male, admitted to a district hospital after ingesting ethanol and pirimiphos-methyl (PM) with suicidal intentions. History included alcoholic cirrhosis with alcoholism, adiposity, diabetes with cerebral microangiopathy, chronic renal insufficiency, heparin-induced thrombocytopenia, and status post necrotizing fasciitis. Emergency medical service reported an alert patient without signs of cholinergic crisis, activated charcoal and atropine were administered. Upon hospital arrival, he received fluid resuscitation, activated charcoal, and atropine. He was transferred to a toxicology unit the next day. On admission, he had no cholinergic signs (dry mucous membranes, warm skin and mydriatic pupils) requiring small atropine doses (0.5mg per hour). Four hours after admission, he developed bradycardia and respiratory distress necessitating intubation. He received atropine by continuous infusion for seven days (248mg total) and obidoxime (bolus and continuous infusion). PM, pirimiphos-methyl-oxon (PMO) and phosphorylated tyrosine (Tyr) adducts derived from human serum albumin were analyzed in vivo. Cholinesterase status (acetylcholinesterase (AChE), butyrylcholinesterase (BChE), inhibitory activity of patient plasma and reactivatability, phosphorylated BChE-derived nonapeptides) was measured in vivo. Obidoxime and atropine were monitored. PM and PMO were detectable, PM with maximum concentration ~24h post admission (p.a.), PMO at ~18h p.a. Tyr-adducts were detectable. AChE in vivo was suppressed on admission, increased continuously after start of obidoxime and reached maximum activity after ~30h. AChE in vivo and reactivatability remained at the same level until the end of monitoring. BChE was already suppressed on admission, termination of the antidote treatment was possible after BChE had recovered to 1/5th of its normal value and extubation was possible after BChE had recovered to 2/5th. While a substantial part of BChE was already aged on admission, ageing continued peaking at ~24h p.a. After initiating obidoxime treatment, plasma levels increased until obidoxime plasma levels reached a steady state. On admission, plasma atropine level was low, it increased with the start of the continuous infusion. Afterwards, the level dropped to a steady state. The clinical course was characterized by bouts of pneumonia necessitating re-intubation and prolonged ventilation, sepsis, delirium, and a peripheral neuropathy. After psychiatric evaluation, the patient was discharged to a neurological rehabilitation facility after 77 days of hospital care.